Video Evaluation of Self-Regulation Skills in Preschool Aged Children with Developmental Delays: Can the impact of Tumbling Together be Measured? - Amelie Fournier; Cecile Loiselle; Jean Chamberlain; Patricia E. Longmuir (Sapientia Publishing Group, 2018)
OBJECTIVES This study evaluated the feasibility of video recording to evaluate an innovative, multi-disciplinary exercise medicine intervention, called Tumbling TogetherTM, on the self-regulation skills required for successful group participation. METHODS A photographer, who did not interact with participants and maintained a consistent position outside of the program area, used a digital video camera to record the program activities. Response to a stop command (attempts after the signal), ability to wait for a turn (yes/no), and ability to line up (correct/incorrect position) were the indicators of self-regulation. Video recordings were analyzed to determine each child's baseline (first two sessions) and post-program (last two sessions) abilities. Chisquare and t-tests identified differences in performance from beginning to end of the program. RESULTS Video recordings were analyzed for 27 children (3 (11%) female, 3.1 to 4.8 years of age) with complex communication/developmental challenges. Response to a stop command improved by 38% (Pre: 2.1 ± 0.9; Post: 1.3 ± 0.4; p<.001). Correct response to a line up signal improved from 26% to 89% (p<.001). The ability to wait for a turn when required increased from 7% to 80% (p<.001). CONCLUSIONS Video recordings suitable for analysis were obtained during all sessions. Children's skills performed during the first two classes were similar. Their skills improved between the start and end of the program. Video recordings accurately reflected the improved performance subjectively reported by therapists and parents. Therefore, video recording appears to be an appropriate method of evaluating the impact of exercise medicine interventions, such as Tumbling TogetherTM, that are designed to enhance the self-regulation skills of preschool children. Research comparing Tumbling participants to children not offered the program, and examining whether the self-regulation skills improved during Tumbling participation would generalize to other settings is required.